Progress of Platelet Derivatives for Cartilage Tissue Engineering - Wu, Siyu; Guo, Wenlai; Li, Rui; Zhang, Xi; Qu, Wenrui (Frontiers in Bioengineering and Biotechnology, 2022)
Articular cartilage has limited self-regeneration ability for lacking of blood vessels, nerves, and lymph, that makes it a great challenge to repair defects of the tissue and restore motor function of the injured or aging population. Platelet derivatives, like platelet-rich plasma, have been proved effective, safety, and economical in musculoskeletal diseases for their autologous origin and rich in growth factors. The combination of platelet derivatives with biomaterials provides both mechanical support and localized sustained release of bioactive molecules in cartilage tissue engineering and low-cost efficient approaches of potential treatment. In this review, we first provide an overview of platelet derivatives and their application in clinical and experimental therapies, then we further discuss the techniques of the addition of platelet derivatives and their influences on scaffold properties. Advances in cartilage tissue engineering with platelet derivatives as signal factors and structural components are also introduced before prospects and concerns in this research field. In short, platelet derivatives have broad application prospects as an economical and effective enhancement for tissue engineering-based articular cartilage repair.